Energy Efficient Routing Algorithm for UWSN - A Clustering Approach - Khan, Gulista; Gola, Kamal Kumar; Ali, Wajid (2015 Second International Conference on Advances in Computing and Communication Engineering, 2015)
Wireless sensor network (WSN) distributed to keep watch on physical or environmental conditions, such as temperature, sound, earthquake or any natural disaster. Sensor nodes Collect and transfer their location through the network to a Base Station. Wireless sensor networks expected to support military applications as well as to civilians. Among the Wireless sensor networks areas underwater Sensing is most crucial. Underwater Wireless Sensor Networks (UWSNs) are used to get the information of underwater environment. UWSNs due to the use of acoustic signals as its physical medium for communications, limited the designing of communication protocols. Most of the routing protocols are based on localization of sensor nodes. But maintain the location in case of UWSN is most important issue. So in this paper propose a routing protocol named Energy efficient routing for UWSNs-A Clustering Approach (EERU-CA). EERU-CA uses the concept of special nodes which act as cluster heads. If no cluster head found, it uses neighbor method to transmit data. Also it is using the concept of CDMA to receive data from various sensor nodes and special nodes. Through simulation study using NS-2 simulator, we proved the significant improvement in term of, Node dead ratio, Energy consumption.